Collective Traumas and the Development of Leader Values: A Currently Omitted, but Increasingly Urgent, Research Area - Tcholakian, Lara A.; Khapova, Svetlana N.; van de Loo, Erik; Lehman, Roger (Frontiers in Psychology, 2019)
The number of traumatic events that occur worldwide is increasing, yet the literature pays little attention to their implications for leader development. This paper calls for a consideration of how collective trauma such as genocides and the Holocaust can shape the cognition of leaders who are second- and third-generation descendants. Drawing on research on the transgenerational transmission of collective trauma, social learning, social identity and psychodynamic theories, we identify three mechanisms through which collective trauma can be transmitted to leaders: cultural artifacts, community events and family narratives. In this article, we introduce the topic of collective trauma in leader development and draw on the theories of psychodynamic, social identity and social learning to explain how the transmission of collective trauma occurs. We also propose how the transmitted trauma shapes leader cognition, values and behaviors. This framework can serve as a basis for future theory-building in leader and leadership development that will be key to the study of authentic and ethical leadership.